Thermo-chemical conversion of waste glass into non-vitreous porous material for adsorption application - Hussain, Z. (Springer Tokyo, 2019)
In the presented work, waste glass was converted into highly porous material through a thermo-chemical reaction. In this conversion, lime was used as flux, salt as a medium and soda as a reactant. The effect of relative concentration of fluxes and reactants on the physicochemical properties of the resulting material were investigated at different temperatures. The porous material product was investigated for its textural and chemical nature using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), Fourier Transform infrared spectroscopy (FT-IR) and X ray florescence spectroscopy. SEM analysis showed that the adsorbent had mesoporous and microporous nature. Since porous glass of well-defined pore size and porosity level was fabricated through a hetero-coagulation template processing, the strategy can be developed into a general pathway to prepare various porous inorganic materials with well-defined pore structure. The porous product was also used as an adsorbent for the removal of direct blue dye from aqueous medium. The glass adsorbent significantly removed the Direct blue dye from the aqueous medium. It was observed that the adsorbent can remove 1.27Â mg/g of dye after 25Â min of treatment. Â© 2019, Springer Japan KK, part of Springer Nature.